Dream horse [videorecording (DVD)] - Collette, Toni; Lewis, Damian, 1971-; Teale, Owen, 1961-; Davison, Peter, 1951- (Universal Pictures Home Entertainment, 2021)
Experience the inspiring true story of Dream Alliance, an unlikely racehorse bred by small-town bartender Jan Vokes. With little money and no experience, Jan convinces her neighbors to chip in their meager earnings to raise Dream and compete against the racing elites, becoming a beacon of hope in their struggling community as he rises through the ranks.